TURKISH VALIDITY AND REABILITY OF SENİORS' SELF-ADMİNİSTRATİON OF THE ELDER ABUSE SUSPİCİON INDEX (Third Sector Social Economic Review, 2021)
Aim: The aim of this study is to determine Turkish reliability and validity of the EASI-SA that is used to determine abuse risk in elderly people, adapting it to Turkish language.Materials and Methods: The sample of the study consisted of 1689 individuals aged 65 and over, who lived in their home environments in the Turkish society and volunteered to participate in the study. The data were collected by answering the form questions sent via smartphone. Since the correlation between the questions of five-item scale was weak, the correlation reliability coefficient was also low (Cronbach’s Alpha=0.474)..As a result, the scale was found to have a “low degree of reliability”; in these circumstances, we can recommend the use of the scale in primary care as well as further community surveys, incidence and prevalence studies. Thus, the Turkish form will be used to determine elderly abuse risk in health programs for elderly people in nursing home, geriatric care centers, day care centers, hospitals and community and promote their quality of life.The validity and reliability study of the scale can be administered to groups of similar ages with different characteristics and be used in prevalence studies.
Keywords: Elderly Abuse; scale; screening; validity and reliability